Characterization of anisotropic human hair keratin scaffolds fabricated via directed ice templating - Zhao, Zhitong (2021)
Human hair keratin (HHK) is successfully exploited as raw materials for 3D scaffolds for soft tissue regeneration owing to its excellent biocompatibility and bioactivity. However, most HHK scaffolds are not able to achieve the anisotropic mechanical properties of soft tissues such as tendons and ligaments due to lack of tunable, well-defined microstructures. In this study, directed ice templating method is used to fabricate anisotropic HHK scaffolds that are characterized by aligned pores (channels) in between keratin layers in the longitudinal plane. In contrast, pores in the transverse plane maintain a homogenous rounded morphology. Channel widths throughout the scaffolds range from ≈5 to ≈15 µm and are tunable by varying the freezing temperature. In comparison with HHK scaffolds with random, isotropic pore structures, the tensile strength of anisotropic HHK scaffolds is enhanced significantly by up to fourfolds (≈200 to ≈800 kPa) when the tensile load is applied in the direction parallel to the aligned pores. In vitro results demonstrate that the anisotropic HHK scaffolds are able to support human dermal fibroblast adhesion, spreading, and proliferation. The findings suggest that HHK scaffolds with well-defined, aligned microstructure hold promise as templates for soft tissues regeneration by mimicking their anisotropic properties.